THE ROLE OF FINANCIAL CALCULATIONS IN THE AUDIT PROCESS - Nurmetov Nurmat Aminbaevich (Western European Studies, 2024)
Financial calculations are fundamental to the audit process, serving as tools to verify the accuracy of financial statements and assess an organization’s financial integrity. This article explores the role of financial calculations in auditing, detailing common methods, practical examples, and challenges faced by auditors. The study emphasizes the importance of precise calculations in maintaining transparency, compliance, and stakeholder trust.
Keywords: Audit; financial calculations; compliance